Tanshinone nanogel and its preparation method and application
By reacting tanshinone IIA with chitosan and sodium tripolyphosphate to form a nanogel, the problem of poor solubility and stability of tanshinone IIA is solved, significantly improving its anti-biofilm and biofilm permeability, and enhancing the lethality of mutant streptococci.
Patent Information
- Application Number
- CN202310288377.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-03-23
AI Technical Summary
The existing tanshinone IIA has extremely poor solubility and poor stability in water, resulting in low bioavailability and difficulty in effectively combating mutant streptococci and its biofilms.
Nanogels are formed by reacting tanshinone IIA with chitosan (CS) and sodium tripolyphosphate (TPP) at room temperature to improve their stability and biofilm permeability.
It significantly improves the anti-biofilm capability and biofilm permeability of tanshinone IIA, enhances its lethality to mutant Streptococcus, and improves its stability in different environments.
Smart Images

Figure CN116196268B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedicine, and in particular relates to research and application of plant extracts in oral anti-inflammatory and antibacterial properties, and specifically relates to a tanshinone nanogel and a preparation method and application thereof. Background Art
[0002] Dental caries (tooth decay) is one of the most common diseases in humans. The World Health Organization (WHO) lists it as one of the three major diseases that endanger human health. A large amount of research data at home and abroad shows that dental caries is a bacterial infection disease caused by Streptococcus mutans and Streptococcus marginale, and Streptococcus mutans has been recognized by scholars at home and abroad as the most important and main pathogen causing caries. Streptococcus mutans can use carbohydrates in the diet, especially sucrose, to create an acidic microenvironment to demineralize tooth enamel and promote their co-aggregation with other harmful microorganisms to form biofilms.
[0003] Biofilms are microbial communities enclosed in extracellular polymeric substances (EPS) and colonized on the surface of materials. EPS can serve as an effective metabolic and physical barrier to prevent antibiotics or antimicrobial agents from penetrating into the biofilm. When treating biofilm-related bacterial infections, high antibiotic doses (about 10 to 1000 times the concentration effective against planktonic bacteria) and longer treatment times are usually required, which may aggravate toxicity and drug resistance, and also pose a huge challenge to the antibiotic treatment of dental caries. Fluoride is currently the most commonly used preparation for the prevention of dental caries, but with the use of fluoride, more and more problems have also emerged. For example, the stability of fluoride concentration in fluoride toothpaste, bacterial fluoride resistance caused by long-term use of fluoride products, and mutations in bacterial genomes, all of which lead to a decrease in the anti-caries effect of fluoride; improper use of fluoride can also lead to acute and chronic poisoning of organisms, posing a huge threat to the health of users. These factors have greatly hindered the promotion of fluoride in the field of dental caries prevention. The market urgently needs products for treating and preventing tooth decay that have good stability, strong ability to kill caries-causing bacteria and are almost harmless to the human body, as substitutes for fluoride-containing products and antibiotics.
[0004] In recent years, plant extracts have received increasing attention as green antibacterial agents and environmentally friendly alternatives in preventing adhesion and destroying biofilms. Some traditional Chinese herbal medicines (such as Danshen) have the ability to inhibit bacterial growth and bacterial adhesion, and can achieve antibacterial effects similar to antibiotics. Danshen, honeysuckle, propolis, platycodon, licorice, etc. have always been considered to have good antibacterial and anti-inflammatory effects in traditional Chinese medicine research, and their composite preparations have been used in oral anti-inflammatory and antibacterial aspects. At present, the active ingredient of Danshen in the composite reagents on the market is mainly crude tanshinone, and there is no report on the use of the fat-soluble components in the refined crude tanshinone as the main active ingredient in the treatment of oral caries.
[0005] Tanshinone IIA (TA) has been shown to be effective in antibacterial and anti-inflammatory activities in vitro. However, TA has extremely poor solubility in water, only 2.8 ng / mL; TA also has very poor stability and will decompose and become inactive under external conditions. This makes traditional danshen preparations difficult to be absorbed by the human body and has the problem of extremely low bioavailability. Therefore, exploring ways to improve the bioavailability of TA, especially to improve its effect on biofilms, is a very meaningful study. Summary of the invention
[0006] The purpose of the present invention is to provide a tanshinone nanogel and a preparation method thereof, so as to enhance the activity of TA against mutans streptococci and their biofilms, and improve the resource utilization of TA, a traditional Chinese medicine ingredient. In order to achieve this purpose, the scheme of the present invention is as follows:
[0007] A tanshinone nanogel is obtained by reacting a TA ethanol solution with a CS solution at room temperature, cross-linking with TPP, and then purifying and freeze-drying. The room temperature is 20°C to 35°C (this is one of the key parameters of the present invention. When the temperature is low, flocculation will occur. When the temperature is too high, TA will be destroyed, and TA has poor thermal stability); the mass ratio of TA to CS is 1:5 to 1:10 (if it is lower than 1:5, less TA will lead to low encapsulation rate. If it is higher than 1:10, more TA will lead to limited drug loading rate, which will lead to drug waste); the mass ratio of TPP to CS is 1:3 to 1:5 (this is one of the key parameters of the present invention. The preparation of the nanogel relies on The electrostatic interaction between CS and TPP, the ratio of the two will affect the intensity of the electrostatic interaction, directly affect the particle size and potential of the nanoparticles, which is the optimal choice of the present invention); the CS solution is a 1% glacial acetic acid solution of CS, and the pH value is adjusted to 4.0-6.0 by adding alkali (this pH selection is one of the key parameters of the present invention. Chitosan is soluble in acidic solution. Too high pH will cause nano-flocculation precipitation, while too low pH will cause chitosan to be very soluble and nanoparticles cannot be formed, and there is no opalescence phenomenon (Tyndall effect) during the preparation process); the TA represents tanshinone IIA, the CS represents chitosan, and the TPP represents sodium tripolyphosphate.
[0008] The method for preparing the tanshinone nanogel comprises the following steps:
[0009] Preparation of TA@CS crude solution: adding TA ethanol solution dropwise to CS solution, stirring while adding, and setting the temperature to 20°C to 35°C; after the addition, adding TPP solution dropwise to the mixed solution, and continuing to stir to obtain TA@CS crude solution; the mass ratio of TA to CS is 1:5 to 1:10; the mass ratio of TPP to CS is 1:3 to 1:5; the CS solution is a 1% glacial acetic acid solution of CS adjusted to pH 4.0 to 6.0 by adding alkali;
[0010] Purification of crude TA@CS solution: The crude TA@CS solution was centrifuged at -4°C, 4000g to 6000g, and the precipitate was collected. The precipitate was resuspended in deionized water and centrifuged again, and the precipitate was collected to obtain a purified TA@CS product.
[0011] Acquisition of TA@CS nanogel: The purified TA@CS is subjected to low-temperature freezing treatment to obtain solid ice cubes, the temperature range of which is 0 to -80°C, and then freeze-dried in a freeze dryer until the solid ice cubes are completely converted into powder, which is the finished product of the tanshinone nanogel. Abbreviation: TA@CS nanogel.
[0012] Further optimization, preparation of CS solution: CS was dissolved in 1% (v / v) glacial acetic acid solution to prepare a solution with a concentration of 0.5-1.0 mg / mL, stirred overnight for protonation, and the pH was adjusted to 4.0-6.0 with 10% NaOH solution. The CS concentration affects the particle size and potential of the nanoparticles, so 0.5-1.0 mg / mL is the preferred effective concentration.
[0013] Further, the preparation of TA ethanol solution: TA is dissolved in anhydrous ethanol to obtain a solution with a concentration of 0.5-1.0 mg / mL.
[0014] Further, the TPP solution was prepared by dissolving TPP in deionized water to prepare a solution with a concentration of 0.5 to 1.0 mg / mL.
[0015] Furthermore, the stirring in the preparation of the TA@CS crude solution is stirring with a magnetic stirrer at a stirring rate of 600 rpm.
[0016] The beneficial effects of the present invention are:
[0017] The nanogel of the present invention not only has good stability and water solubility, but also has significantly improved anti-biofilm ability. The specific performance is as follows:
[0018] The nanogel of the invention enhances the anti-biofilm capability of TA, and the anti-biofilm capability of the nanogel is significantly enhanced on the basis of the original single free substance.
[0019] The nanogel of the invention enhances the biomembrane permeability of TA, and the biomembrane permeability of the nanogel is significantly enhanced on the basis of the original single free substance.
[0020] The nanogel of the present invention has biomembrane targeting in an acidic environment, and the pH-responsive biomembrane targeting avoids the influence of drugs on cells in a normal physiological environment.
[0021] The preparation conditions of the nanogel of the invention are mild, without high temperature and high pressure conditions, and without the participation of toxic reagents, thereby reducing the loss of TA in the preparation process and improving the utilization rate of the fat-soluble components of tanshinone.
[0022] Compared with single free TA, the nanogel of the present invention has improved high temperature stability, pH stability, room temperature stability and light stability.
[0023] The nanogel of the present invention has an average particle size Z-average of 393.97±13.92nm, a potential Zeta-potential of +42.27±1.25mV, a dispersion index PDI of 0.18, and has good structural stability and dispersion characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the scanning electron microscopy image of TA@CS nanogel;
[0025] Figure 2 The samples of the nanogels prepared in Comparative Example 1 (left) and Comparative Example 2 (right);
[0026] Figure 3 The storage stability diagram of free TA and TA@CS nanogel in different environments;
[0027] Figure 3 A~ Figure 3 E is the statistical graph of the data treated under natural light, 80°C and different pH (4.5, 7.0 and 8.5);
[0028] Figure 4 The drug release curves of TA@CS nanogels in media with different pH values;
[0029] Figure 5 The data graph shows the inhibition rate of free TA and TA@CS nanogel on biofilm formation;
[0030] Figure 6 The potential diagram of the biofilm after co-incubation of TA@CS nanogel and biofilm;
[0031] Figure 7 The scanning electron microscopy image of the biofilm after co-incubation of TA@CS nanogel and biofilm;
[0032] Figure 8 Laser confocal images of biofilm after co-incubation of free TA, TA@CS nanogel and biofilm;
[0033] Fig. 9 This is an analysis of the red-green fluorescence ratio in the longitudinal section of the laser confocal image of the biofilm after free TA, TA@CS nanogel and biofilm were co-incubated. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with the implementation examples and the accompanying drawings. However, the present invention is not limited to the following implementation examples. The concentrations and percentages involved in the following case appendix all refer to TA.
[0035] Example 1
[0036] A method for preparing tanshinone nanogel, the preparation method comprising the following steps:
[0037] Solution preparation: accurately weigh a certain mass of CS, dissolve it in 1% (v / v) glacial acetic acid solution to prepare a CS solution with a concentration of 1.0 mg / mL, stir overnight for protonation, adjust the pH to 6.0 with 10% NaOH solution to prepare a CS solution; accurately weigh 5 mg of TA and dissolve it in 10 mL of anhydrous ethanol to prepare a 0.5 mg / mL TA ethanol solution; accurately weigh 5 mg of TPP and dissolve it in 10 mL of deionized water to prepare a 0.5 mg / mL TPP solution.
[0038] Preparation of TA@CS crude solution: Take 8 mL of TA ethanol solution; add it dropwise into 40 mL of 1 mg / mL CS solution at a mass ratio of 1:10, place it on a magnetic stirrer, set the temperature to 20°C, stir while adding, and the speed is 600 rpm / min. The addition is completed after 20 minutes; add 20 mL of TPP solution dropwise into the mixed solution at a mass ratio of 1:4 (TPP:CS), and stir magnetically for 30 minutes.
[0039] Purification of crude TA@CS solution: The crude TA@CS solution was centrifuged at -4°C and 5000 g to obtain an orange-red precipitate, and the supernatant was discarded. The precipitate was resuspended in deionized water and centrifuged again to obtain a purified TA@CS product.
[0040] Obtaining TA@CS nanogel: Put the purified TA@CS into a -20°C refrigerator, freeze it into ice cubes, and then put it into a freeze dryer for freeze drying until all the ice cubes are converted into powder, thereby obtaining the tanshinone nanogel product, referred to as TA@CS nanogel.
[0041] Example 2
[0042] A method for preparing tanshinone nanogel, the preparation method comprising the following steps:
[0043] Solution preparation: Accurately weigh a certain mass of CS, dissolve it in 1% (v / v) glacial acetic acid solution to prepare a CS solution with a concentration of 1.0 mg / mL, stir overnight for protonation, adjust the pH to 5.0 with 10% NaOH solution to prepare a CS solution; accurately weigh 5 mg of TA and dissolve it in 10 mL of anhydrous ethanol to prepare a 0.5 mg / mL TA ethanol solution; accurately weigh 10 mg of TPP and dissolve it in 10 mL of deionized water to prepare a 1 mg / mL TPP solution.
[0044] Preparation of TA@CS crude solution: Take 8 mL of TA ethanol solution; add it dropwise into 40 mL of 1 mg / mL CS solution at a mass ratio of 1:10, place it on a magnetic stirrer, set the temperature to 25°C, stir while adding, and the speed is 600 rpm / min. The addition is completed after 20 minutes; add 10 mL of TPP solution dropwise into the mixed solution at a mass ratio of 1:4 (TPP:CS), and stir magnetically for 30 minutes.
[0045] Purification of crude TA@CS solution: The crude TA@CS solution was centrifuged at -4°C and 6000 g to obtain an orange-red precipitate, and the supernatant was discarded. The precipitate was resuspended in deionized water and centrifuged again to obtain a purified TA@CS product.
[0046] Obtaining TA@CS nanogel: Put the purified TA@CS into a -20°C refrigerator, freeze it into ice cubes, and then put it into a freeze dryer for freeze drying until all the ice cubes are converted into powder, thereby obtaining the tanshinone nanogel product, referred to as TA@CS nanogel.
[0047] Example 3
[0048] A method for preparing tanshinone nanogel, the preparation method comprising the following steps:
[0049] Solution preparation: accurately weigh a certain mass of CS, dissolve it in 1% (v / v) glacial acetic acid solution to prepare a CS solution with a concentration of 0.6 mg / mL, stir overnight for protonation, adjust the pH to 4.0 with 10% NaOH solution to prepare a CS solution; accurately weigh 10 mg of TA and dissolve it in 10 mL of anhydrous ethanol to prepare a 1 mg / mL TA ethanol solution; accurately weigh 10 mg of TPP and dissolve it in 10 mL of deionized water to prepare a 1 mg / mL TPP solution.
[0050] Preparation of TA@CS crude solution: Take 3 mL of TA ethanol solution; add it dropwise into 50 mL of 0.6 mg / mL CS solution at a mass ratio of 1:10, place it on a magnetic stirrer, set the temperature to 30°C, stir while adding, and the speed is 600 rpm / min. The addition is completed after 20 minutes; add 10 mL of TPP solution dropwise into the mixed solution at a mass ratio of 1:3 (TPP:CS), and stir magnetically for 30 minutes.
[0051] Purification of crude TA@CS solution: The crude TA@CS solution was centrifuged at -4°C and 4000 g to obtain an orange-red precipitate, and the supernatant was discarded. The precipitate was resuspended in deionized water and centrifuged again to obtain a purified TA@CS product.
[0052] Obtaining TA@CS nanogel: Put the purified TA@CS into a -20°C refrigerator, freeze it into ice cubes, and then put it into a freeze dryer for freeze drying until all the ice cubes are converted into powder, thereby obtaining the tanshinone nanogel product, referred to as TA@CS nanogel.
[0053] Example 4
[0054] A method for preparing tanshinone nanogel, the preparation method comprising the following steps:
[0055] Solution preparation: Accurately weigh a certain mass of CS, dissolve it in 1% (v / v) glacial acetic acid solution to prepare a CS solution with a concentration of 0.8 mg / mL, stir overnight for protonation, adjust the pH to 5.0 with 10% NaOH solution to prepare a CS solution; accurately weigh 10 mg of TA and dissolve it in 10 mL of anhydrous ethanol to prepare a 1 mg / mL TA ethanol solution; accurately weigh 5 mg of TPP and dissolve it in 10 mL of deionized water to prepare a 0.5 mg / mL TPP solution.
[0056] Preparation of TA@CS crude solution: Take 4 mL of TA ethanol solution; add it dropwise into 50 mL of 0.8 mg / mL CS solution at a mass ratio of 1:10, place it on a magnetic stirrer, set the temperature to 20°C, stir while adding, and the speed is 600 rpm / min. The addition is completed after 20 minutes; add 16 mL of TPP solution dropwise into the mixed solution at a mass ratio of 1:5 (TPP:CS), and stir magnetically for 30 minutes.
[0057] Purification of crude TA@CS solution: The crude TA@CS solution was centrifuged at -4°C and 6000 g to obtain an orange-red precipitate, and the supernatant was discarded. The precipitate was resuspended in deionized water and centrifuged again to obtain a purified TA@CS product.
[0058] Obtaining TA@CS nanogel: Put the purified TA@CS into a -20°C refrigerator, freeze it into ice cubes, and then put it into a freeze dryer for freeze drying until all the ice cubes are converted into powder, thereby obtaining the tanshinone nanogel product, referred to as TA@CS nanogel.
[0059] Comparative Example 1
[0060] In this comparative example, only the mass ratio of TPP:CS is changed relative to that in Example 1, and other operations and parameters are the same as those in Example 1.
[0061] A method for preparing tanshinone nanogel, the preparation method comprising the following steps:
[0062] Solution preparation: Accurately weigh a certain mass of CS, dissolve it in 1% (v / v) glacial acetic acid solution to prepare a CS solution with a concentration of 1 mg / mL, stir overnight for protonation, adjust the pH to 6.0 with 10% NaOH solution to prepare a CS solution; accurately weigh 5 mg of TA and dissolve it in 10 mL of anhydrous ethanol to prepare a 0.5 mg / mL TA ethanol solution; accurately weigh 5 mg of TPP and dissolve it in 10 mL of deionized water to prepare a 0.5 mg / mL TPP solution.
[0063] Preparation of TA@CS crude solution: Take 8 mL of TA ethanol solution; add it dropwise into 40 mL of 1 mg / mL CS solution at a mass ratio of 1:10, place it on a magnetic stirrer, set the temperature to 20°C, stir while adding, and the speed is 600 rpm / min. The addition is completed after 20 minutes; add 20 mL of TPP solution dropwise into the mixed solution at a mass ratio of 1:2 (TPP:CS), and stir magnetically for 30 minutes.
[0064] Purification of crude TA@CS solution: The crude TA@CS solution was centrifuged at -4°C and 5000 g to obtain an orange-red precipitate, and the supernatant was discarded. The precipitate was resuspended in deionized water and centrifuged again to obtain a purified TA@CS product.
[0065] Obtaining TA@CS nanogel: Put the purified TA@CS into a -20°C refrigerator, freeze it into ice cubes, and then put it into a freeze dryer for freeze drying until all the ice cubes are converted into powder, thereby obtaining the tanshinone nanogel product, referred to as TA@CS nanogel.
[0066] Comparative Example 2
[0067] In this comparative example, only the mass ratio of TPP:CS is changed compared with Example 3, and other operations and parameters are the same as Example 1.
[0068] A method for preparing tanshinone nanogel, the preparation method comprising the following steps:
[0069] Solution preparation: accurately weigh a certain mass of CS, dissolve it in 1% (v / v) glacial acetic acid solution to prepare a CS solution with a concentration of 0.6 mg / mL, stir overnight for protonation, adjust the pH to 4.0 with 10% NaOH solution to prepare a CS solution; accurately weigh 10 mg of TA and dissolve it in 10 mL of anhydrous ethanol to prepare a 1 mg / mL TA ethanol solution; accurately weigh 10 mg of TPP and dissolve it in 10 mL of deionized water to prepare a 1 mg / mL TPP solution.
[0070] Preparation of TA@CS crude solution: Take 3 mL of TA ethanol solution; add it dropwise into 50 mL of 0.6 mg / mL CS solution at a mass ratio of 1:10, place it on a magnetic stirrer, set the temperature to 30°C, stir while adding, and the speed is 600 rpm / min. The addition is completed after 20 minutes; add 10 mL of TPP solution dropwise into the mixed solution at a mass ratio of 1:6 (TPP:CS), and stir magnetically for 30 minutes.
[0071] Purification of crude TA@CS solution: The crude TA@CS solution was centrifuged at -4°C and 4000 g to obtain an orange-red precipitate, and the supernatant was discarded. The precipitate was resuspended in deionized water and centrifuged again to obtain a purified TA@CS product.
[0072] Obtaining TA@CS nanogel: Put the purified TA@CS into a -20°C refrigerator, freeze it into ice cubes, and then put it into a freeze dryer for freeze drying until all the ice cubes are converted into powder, thereby obtaining the tanshinone nanogel product, referred to as TA@CS nanogel.
[0073] The nanogels obtained in the embodiments and comparative examples were tested, and the test items were as follows:
[0074] Test Item 1
[0075] Morphological characterization of nanogels:
[0076] After the prepared nanogel was sprayed with gold, the morphology of the nanogel was observed using a scanning electron microscope. Figure 1 As shown: the nanogels of Examples 1 to 4 present a uniform spherical structure with a size ranging from 50 to 90 nm.
[0077] Test Item 2
[0078] The prepared nanogels were treated with free TA at 80°C, natural light and different pH values (4.5, 7.0 and 8.5) for 120 min, and samples were collected at different time intervals (0, 20, 40, 60, 80, 100 and 120 min), and the absorbance of the samples was measured at 270 nm using a UV spectrophotometer. The TA retention rate is defined by the following formula:
[0079] Retention rate (%) = C t / C0×100%
[0080] Where: C0 is the initial TA concentration, C t is the TA concentration at a certain time t after treatment.
[0081] The results are as follows Figure 3 As shown in A: After only 120 min of sunlight irradiation, the free TA content dropped sharply to 53.27 ± 0.40%. In contrast, the encapsulated TA content remained above 80%, confirming that the nanogel has a significant physical barrier effect on TA. Compared with the free compound, the encapsulated TA exhibited better thermal stability ( Figure 3 B). After exposure to different pH environments for 120 min, the free TA content decreased significantly. However, after nanogel encapsulation, the residual TA content remained at a high level under the same pH conditions ( Figure 3 C, D, E).
[0082] The results showed that the protective effect of nanogels helps to improve the physical and chemical stability of guest molecules TA during long-term storage, making them more suitable for food processing.
[0083] Test Item 3
[0084] The prepared nanogel was redispersed in 10 ml of dissolution medium containing 40% ethanol (the dissolution medium was pH = 5.0 citrate buffer and pH = 7.4 PBS solution), placed in a dialysis bag (molecular weight cutoff of 8000-14000Da), put into 100 ml of the corresponding dissolution medium, and shaken in a constant temperature water bath at 37°C (120 r·min -1 ), 1 ml of sample was taken at different time points, and the same volume of blank medium was added. The sample was filtered through a 0.22 μm microporous filter membrane and then the content was determined by high performance liquid chromatography. The cumulative release rate was calculated according to the formula as follows.
[0085]
[0086] Where: C t is the concentration of Tanshinone ⅡA in the solution when sampling was performed at time t; C0 is the total concentration of Tanshinone ⅡA in the sample solution.
[0087] The results are as follows Figure 4As shown: the release rate of the prepared nanogel in an acidic environment (pH 5.0) is 98.09%, and the release rate in a physiological environment (pH 7.4) is 76.26%.
[0088] The results showed that the nanogel exhibited sustained-release properties and was pH sensitive, releasing more tanshinone IIA in an acidic environment, which was beneficial for the nanogel to function better in the biofilm environment while reducing its toxic side effects on normal cells.
[0089] Test Item 4
[0090] The prepared nanogel was mixed with 100 μL of bacterial dilution solution (diluted to OD 600 =0.5) were mixed in a 96-well plate and then incubated at 37°C for 4 hours or 24 hours. A layer of white biofilm was visible at the bottom of the 96-well plate. The wells were washed with PBS (pH 7.4) to remove unattached bacteria and culture medium components. The washed biofilm was fixed with 200 μL 10% methanol for 15 minutes and stained with 200 μL 0.25% CV for 30 minutes at room temperature. Subsequently, each well was rinsed with PBS to remove excess dye. The crystal violet-bound biofilm was dissolved with 200 μL 95% ethanol solution. Finally, the OD was measured by an enzyme reader (BioTek, USA). 590 The biofilm analysis was performed on three independent occasions. Figure 5 As shown in the figure: Free TA had a weak effect on biofilm formation, independent of the incubation time. The nanogels had strong anti-biofilm activity and could inhibit biofilm formation for a long time. The long-term efficacy of TA@CS nanogels may be due to their sustained release properties, resulting in continuous inhibition of biofilm formation over 24 hours.
[0091] The results showed that TA@CS nanogel coating could prolong the anti-biofilm performance of guest molecules and TA@CS nanogel could effectively inhibit the formation of biofilm for a long time.
[0092] Test Item 5
[0093] Characterization of biological targeting of nanogels:
[0094] The nanogels prepared in Examples 1 to 4 were incubated with mutans streptococcus biofilms at different pH environments (5.0 and 7.4) for 0.5 h at 37°C, and the changes in the biofilm sites were measured using a dynamic light scattering instrument, and the biofilms were observed under a scanning electron microscope. The results are shown in FIG. Figure 6 , 7 As shown: In a pH 5.0 environment, after the nanogel was co-incubated with the biofilm, the biofilm potential moved toward the positive potential direction, and the nanogel was targetedly adsorbed onto the biofilm, making the biofilm surface rough.
[0095] The results showed that the nanogel had biomembrane targeting properties in an acidic environment.
[0096] Test Item 6
[0097] The nanogels prepared in Examples 1 to 4 were dissolved in PBS with a pH of 5.0, and Streptococcus mutans was cultured in BHIS medium at 37°C for 48 hours without shaking to allow biofilm to form. The biofilm was washed with PBS, and the nanogel and biofilm were co-incubated at 37°C for 2 hours. The biofilm was stained with an AO / EB double staining kit for 15 minutes, and observed under a laser confocal microscope. The green and red fluorescence ratios of the longitudinal sections of the biofilm were analyzed by ImageJ to measure the live / dead rate of bacteria in the bottom layer of the biofilm, and then the penetration effect of the nanogel was quantitatively analyzed. The results are shown in Figure 2. Figure 8 , 9 As shown: the Control group is a blank control group, in which no treatment is performed on the biofilm. The blank control group shows an intact biofilm; free TA has poor penetration in the biofilm and only kills a small number of live bacteria on the top of the biofilm; while TA@CS nanogel is effective throughout the biofilm and can kill almost all bacteria even at the bottom of the biofilm.
[0098] The results showed that nanoencapsulation effectively enhanced the biomembrane permeability of TA, and TA@CS had good biomembrane permeability and could penetrate the biomembrane barrier.
[0099] The TA@CS nanogel prepared in the present invention has an encapsulation rate of 91.41%, a drug loading rate of up to 21.27%, high antibacterial activity, and biomembrane targeting and permeability. At the same time, the present invention has low production cost, simple process, economic savings, and is very suitable for large-scale industrial production. The specific data are summarized in the following table.
[0100] Experimental results:
[0101]
[0102]
[0103]
[0104] [1]PBZhang, SLLi, H.Chen,
[0105] [2]S.Rashki,H.Safardoust-Hojaghan,H.Mirzaei,WKAbdulsahib,MAMahdi,M.Salavati-Niasari,A.Khaledi,A.Khorshidi,SGAMousavi,Delivery LL37bychitosan nanoparticles for enhanced antibacterial and antibiofilm efficacy,Carbohydrate Polymers 291(2022).
[0106] [3] SMWu, C.Xu, YWZhu, L.Zheng, LDZhang, Y.Hu, BRYu, YGWang, FJXu, Biofilm-Sensitive Photodynamic Nanoparticles for Enhanced Penetration and Antibacterial Efficiency, Adv Funct Mater 31(33)(2021).
[0107] Comparative Example 1: During the preparation of the nanogel in Comparative Example 1, due to the excessive addition of TPP, coagulation occurred with the addition of TPP, and the particle size of the final prepared nanogel was micron-level, and a large amount of precipitation appeared after standing for 5 minutes; and due to the introduction of excessive phosphate groups, the prepared nanogel was electronegative.
[0108] Comparative Example 2: In Comparative Example 2, due to the addition of too little TPP, the prepared nanogel has a higher positive potential and good dispersibility, but at the same time, the electrostatic force between CS and TPP is low, and the nanogel particle size is larger. Comparative Example 3: Poly {(9,9-bis (6′-N,N,N-trimethylammonium) hexylfluorene benzene] dibromide} with external positively charged QA groups was synthesized as a model conjugated polymer (PFP) (Results and Discussion, first paragraph), and the biofilm formation rate appeared in the literature Figure 1 .
[0109] Comparative Example 4: Chitosan nanoparticles loaded with LL37 (2.3) were prepared, the biofilm formation rate appeared at 3.5, and the encapsulation efficiency and drug loading rate of the nanoparticles appeared at 3.2.
[0110] Comparative Example 5: RB@PMB@GA nanoparticles were prepared from propylamine-functionalized rose bengal (RB-NH2), polydopamine (PDA), polymyxin B (PMB), and gluconic acid (GA) (Introduction, paragraph 4), and the biomembrane penetration effect appeared at 2.6.
[0111] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A tanshinone nanogel, characterized in that: The TA ethanol solution and the CS solution react at room temperature, then cross-linked by TPP, and then purified and freeze-dried to obtain the product, wherein the room temperature is 20°C to 35°C; The mass ratio of TA to CS is 1:5 to 1:10; The mass ratio of TPP to CS is 1:3 to 1:5; the CS solution is a 1% glacial acetic acid solution of CS, and the pH value is adjusted to 4.0 to 6.0 by adding alkali; the TA represents tanshinone IIA, the CS represents chitosan, and the TPP represents sodium tripolyphosphate; the operation of reacting the TA ethanol solution with the CS solution at room temperature and then cross-linking with TPP is: dropwise adding the TA ethanol solution to the CS solution while stirring, and after the dropwise addition, dropwise adding the TPP solution to the mixed solution, and continuing to stir to obtain a TA@CS crude solution.
2. The method for preparing the tanshinone nanogel according to claim 1, characterized in that: The following steps are involved: Preparation of TA@CS crude solution: Add TA ethanol solution dropwise into CS solution, stirring while adding, and set the temperature to 20℃~35℃; Add drop by drop After that, TPP solution was added dropwise to the mixed solution and stirring was continued to obtain a TA@CS crude solution; The mass ratio of TA to CS is 1:5 to 1:10; The mass ratio of TPP to CS is 1:3 to 1:5; The CS solution is a 1% glacial acetic acid solution of CS adjusted to pH 4.0-6.0 by adding alkali; Purification of crude TA@CS solution: The crude TA@CS solution was centrifuged at -4°C, 4000g to 6000g, and the precipitate was collected. The precipitate was resuspended in deionized water and centrifuged again, and the precipitate was collected to obtain a purified TA@CS product. Acquisition of TA@CS nanogel: The purified TA@CS is subjected to low-temperature freezing treatment to obtain solid ice cubes, the temperature range of which is 0 to -80°C, and then freeze-dried in a freeze dryer until the solid ice cubes are completely converted into powder, which is the finished product of the tanshinone nanogel.
3. The method for preparing tanshinone nanogel according to claim 2, characterized in that: Preparation of CS solution: CS was dissolved in 1% glacial acetic acid solution to prepare a solution with a concentration of 0.5-1.0 mg / mL, stirred overnight for protonation, and the pH value was adjusted to 4.0-6.0 with 10% NaOH solution.
4. The method for preparing tanshinone nanogel according to claim 2, characterized in that: Preparation of TA ethanol solution: Dissolve TA in anhydrous ethanol to obtain a solution with a concentration of 0.5-1.0 mg / mL.
5. The method for preparing tanshinone nanogel according to claim 2, characterized in that: Preparation of TPP solution: Dissolve TPP in deionized water to prepare a solution with a concentration of 0.5-1.0 mg / mL.
6. The method for preparing tanshinone nanogel according to claim 2, characterized in that: The stirring in the preparation of the TA@CS crude solution is performed by a magnetic stirrer at a stirring rate of 600 rpm.
7. The tanshinone nanogel described in claim 1 is used in the preparation of oral and dental anti-inflammatory and antibacterial drugs.
8. The tanshinone nanogel according to claim 1 is used in the preparation of a drug for treating biofilm-related bacterial infections in the oral cavity.
Citation Information
Patent Citations
Total tanshinone composite preparation
CN102100741A
Pharmaceutical composition with effects of preventing and / or treating coronary microvascular disease
CN110613722A
Tanshinone and protein polypeptide composite nanoparticle as well as preparation method and application thereof
CN113769068A
Chitosan or its derivative as drug carrier for carrying red sage root extract
CN1698901A